Iron monatomic catalyst with controllable doping of elements in p region and application of iron monatomic catalyst

By introducing p-zone elements into the Fe-N4 catalyst, regulating the electronic structure of the iron metal center, and building an asymmetric Fe-X1N3 configuration, the problem of low efficiency of traditional catalyst activation PMS is solved, and more efficient catalytic activity and selectivity is achieved, which is suitable for pollutant degradation under different water quality environments.

CN119838622AActive Publication Date: 2025-04-18ZHEJIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510029739.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The symmetry of the electron distribution of traditional Fe-N4 catalysts during catalysis limits the further improvement of their catalytic activity and selectivity, making it difficult to effectively activate persulfate (PMS) to improve oxidation efficiency.

Method used

By introducing p-region elements such as sulfur, phosphorus and boron, the electronic structure and coordination environment of the iron metal center of the catalyst are regulated, and the asymmetric Fe-X1N3 configuration is constructed, breaking the symmetry limitations of the traditional Fe-N4 structure and achieving precise regulation of the PMS activation path.

Benefits of technology

It significantly improves the activation efficiency of PMS and the activity and selectivity of catalysts, enhances the degradation efficiency of phenolic pollutants, and maintains efficient application under different water quality environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838622A_ABST
    Figure CN119838622A_ABST
Patent Text Reader

Abstract

The invention discloses an iron monatomic catalyst with controllable doping of elements in a p region and application of the iron monatomic catalyst. The method comprises the following steps: firstly, mixing doping sources (boric acid, phosphoric acid and sulfuric acid) with ferrous ions, and then adding an organic ligand (oxalic acid) to construct iron complexes with different coordination configurations; the components are organized into a supramolecular precursor with a rod-like structure through a supramolecular self-assembly process of the melamine and the cyanuric acid. In an argon atmosphere, the precursor is subjected to a high-temperature pyrolysis process to synthesize a series of iron monatomic catalysts controllably doped with elements in a p region. By constructing an asymmetric Fe-X1N3 configuration (X represents a doping element) and accurately controlling the doping amount and position of elements in a p region, the coordination structure and electronic characteristics of the Fe monatomic catalyst are effectively regulated and controlled, regulation and control of a persulfate (PMS) activation path are realized, the activity and selectivity of the catalyst are improved, and a new thought is provided for control and treatment of environmental pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material engineering and environmental engineering, and in particular relates to an iron single-atom catalyst with controllable doping of p-zone elements and application thereof. Background Art

[0002] Persulfate (PMS) has a unique asymmetric structure and is easily activated to degrade pollutants. It is a very promising advanced oxidation technology. [1] However, the activation efficiency of PMS is often limited by the structural and electronic properties of the catalyst, which limits its efficiency in practical applications. Rationally designed catalysts will be able to selectively generate 1 O2, high-valent iron species or catalytic oxidation through electron transfer pathways can not only improve oxidation efficiency, but also reduce unnecessary side reactions, providing a greener and more efficient solution for environmental remediation and organic synthesis. However, although traditional Fe-N4 is stable, the symmetry of electron distribution during the catalytic process limits the further improvement of its catalytic activity and selectivity. In order to break this limitation, p-block elements such as sulfur (S), phosphorus (P) and boron (B) are doped to regulate the electronic structure and coordination environment of the iron metal center of the catalyst.

[0003] The introduction of p-block elements provides a new idea for regulating the activation path of PMS. Studies have shown that the doping of p-block elements can significantly change the electron density and d-band center position of Fe SACs, thereby affecting its interaction with PMS. For example, sulfur doping can increase the electron density of Fe atoms and improve their adsorption capacity for PMS, thereby promoting the activation of PMS and generating more reactive oxygen species (ROS). Phosphorus doping may further improve the catalytic efficiency by adjusting the d-band center of Fe atoms and optimizing the adsorption and activation process of PMS. Boron doping, as an effective means of electronic structure regulation, can adjust the electron distribution of Fe-N4 sites and reduce the activation energy barrier of PMS through its unique electronic properties, thereby improving the activity and selectivity of the catalyst.

[0004] It was found that by constructing an asymmetric Fe-X1N3 configuration (X is the doping element) to break the traditional symmetrical coordination structure and precisely control the doping amount and position of the p-zone element, the coordination structure and electronic properties of Fe SACs can be effectively regulated, and the activation path of PMS can be precisely regulated. This doping strategy can not only improve the utilization efficiency of PMS, but also broaden the application range of catalysts under different water environment conditions, opening up new ideas for the control and treatment of environmental pollutants. Summary of the invention

[0005] The purpose of the present invention is to provide an iron single-atom catalyst with controllable doping of p-zone elements and its application in view of the deficiencies of the prior art.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides an iron single-atom catalyst controllably doped with p-zone elements, wherein the iron single-atom catalyst controllably doped with p-zone elements is prepared by the following method:

[0008] S1: dissolving melamine in deionized water at 70-90° C. to obtain a melamine solution; dissolving cyanuric acid in deionized water at 70-90° C. to obtain a cyanuric acid solution; dissolving ferrous sulfate heptahydrate in deionized water at 20-30° C. to obtain a ferrous sulfate solution; the molar ratio of melamine, cyanuric acid and ferrous sulfate is 1:0.5-0.9:0.1-0.5;

[0009] S2: adding sulfuric acid and oxalic acid to the ferrous sulfate solution, and stirring at 20-30° C. for 5-10 min to form a solution A; the molar ratio of the sulfuric acid, oxalic acid and ferrous sulfate is 1:0.8-1:0.2-0.8;

[0010] S3: adding the solution A to the cyanuric acid solution, stirring at 70-90° C. for 5-10 min to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to perform a coprecipitation reaction for 2-4 h; after the reaction is completed, performing solid-liquid separation by suction filtration, and washing the precipitate; then performing forced air drying at 55-60° C. for 6-8 h to obtain a supramolecular precursor, and grinding it into a uniform powder;

[0011] S4: Under the protection of argon atmosphere, the powdered supramolecular precursor is heated to 550-600°C, kept at this temperature for 3-5 hours and then cooled to room temperature to obtain an iron single atom catalyst with controllable doping of p-block elements, denoted as FeS / CN.

[0012] In a second aspect, the present invention further provides an iron single-atom catalyst controllably doped with p-zone elements, wherein the iron single-atom catalyst controllably doped with p-zone elements is prepared by the following method:

[0013] S1: dissolving melamine in deionized water at 70-90° C. to obtain a melamine solution; dissolving cyanuric acid in deionized water at 70-90° C. to obtain a cyanuric acid solution; dissolving ferrous sulfate heptahydrate in deionized water at 20-30° C. to obtain a ferrous sulfate solution; the molar ratio of melamine, cyanuric acid and ferrous sulfate is 1:0.5-0.9:0.1-0.5;

[0014] S2: adding oxalic acid and phosphoric acid to the ferrous sulfate solution, and stirring at 20-30° C. for 5-10 min to form a solution A; the molar ratio of the phosphoric acid, oxalic acid and ferrous sulfate is 1:0.8-1:0.2-0.8;

[0015] S3: adding the solution A to the cyanuric acid solution, stirring at 70-90° C. for 5-10 min to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to perform a coprecipitation reaction for 2-4 h; after the reaction is completed, performing solid-liquid separation by suction filtration, and washing the precipitate; then performing forced air drying at 55-60° C. for 6-8 h to obtain a supramolecular precursor, and grinding it into a uniform powder;

[0016] S4: Under the protection of an argon atmosphere, the powdered supramolecular precursor is heated to 550-600°C, kept at this temperature for 3-5 hours, and then cooled to room temperature to obtain an iron single atom catalyst with controllable doping of p-block elements, which is denoted as FeP / CN.

[0017] In a third aspect, the present invention further provides an iron single-atom catalyst controllably doped with p-zone elements, wherein the iron single-atom catalyst controllably doped with p-zone elements is prepared by the following method:

[0018] S1: dissolving melamine in deionized water at 70-90° C. to obtain a melamine solution; dissolving cyanuric acid in deionized water at 70-90° C. to obtain a cyanuric acid solution; dissolving ferrous sulfate heptahydrate in deionized water at 20-30° C. to obtain a ferrous sulfate solution; the molar ratio of melamine, cyanuric acid and ferrous sulfate is 1:0.5-0.9:0.1-0.5;

[0019] S2: adding boric acid to the ferrous sulfate solution and stirring at 20-30° C. for 5-10 min to form a solution A; the molar ratio of the boric acid, oxalic acid and ferrous sulfate is 1:0.8-1:0.2-0.8;

[0020] S3: adding the solution A to the cyanuric acid solution, stirring at 70-90° C. for 5-10 min to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to perform a coprecipitation reaction for 2-4 h; after the reaction is completed, performing solid-liquid separation by suction filtration, and washing the precipitate; then performing forced air drying at 55-60° C. for 6-8 h to obtain a supramolecular precursor, and grinding it into a uniform powder;

[0021] S4: Under the protection of argon atmosphere, the powdered supramolecular precursor is heated to 550-600°C, kept at this temperature for 3-5 hours and then cooled to room temperature to obtain an iron single atom catalyst with controllable doping of p-block elements, denoted as FeB / CN.

[0022] In a fourth aspect, the present invention also provides an application of an iron single-atom catalyst with controllable doping of p-zone elements in removing phenolic benzene series substances from surface water, specifically: pouring the iron single-atom catalyst with controllable doping of p-zone elements and permonosulfate into surface water containing phenolic benzene series substances, the water temperature is 20-30°C, stirring the reaction for 10-15 minutes, and completing the removal of phenolic benzene series substances from the surface water; the dosage of the iron single-atom catalyst with controllable doping of p-zone elements is 0.2-0.6 g / L; the dosage of the permonosulfate is 100-600 μmol / L; the concentration of the phenolic benzene series substances in the surface water is 0-200 μmol / L.

[0023] Furthermore, the phenolic benzene series compound is phenol, p-chlorophenol, p-hydroxybenzoic acid or p-nitrophenol.

[0024] The beneficial effects of the present invention are:

[0025] 1) By changing the type of doping elements, the controllable synthesis of iron single atoms doped with different p-block elements was achieved, and the efficiency of catalyst activation PMS, the type and content of active species generated were analyzed;

[0026] 2) Doping with different elements changes the charge density of the Fe metal center and the position of the d-band center, optimizes the interaction between the catalyst and PMS, enhances the activation ability of the catalyst for PMS, and improves the degradation efficiency of phenolic pollutants;

[0027] 3) By precisely controlling the position of the doping elements, an asymmetric Fe-X1N3 configuration is constructed, breaking the symmetry restrictions of the traditional Fe-N4 structure, and achieving precise regulation of the PMS activation pathway from singlet oxygen, high-valent iron, and electron transfer pathways;

[0028] 4) It has good adaptability and stability, and can maintain high efficiency in removing chlorophenols in different water quality environments, while being able to efficiently remove a variety of phenolic benzene derivatives. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the structure of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0030] Figure 2 A spherical aberration-corrected high-angle annular dark-field scanning transmission electron micrograph and a Fe and S element distribution spectrum of the sulfur-doped iron single-atom catalyst prepared in Example 4;

[0031] Figure 3 A spherical aberration-corrected high-angle annular dark-field scanning transmission electron micrograph and a Fe and S element distribution spectrum of the phosphorus-doped iron single-atom catalyst prepared in Example 7;

[0032] Figure 4 A spherical aberration-corrected high-angle annular dark-field scanning transmission electron micrograph and a Fe and B element distribution spectrum of the boron-doped iron single-atom catalyst prepared in Example 11;

[0033] Figure 5 is the three-dimensional intensity distribution and line profile analysis diagram, where Figure 5 (a) is the three-dimensional intensity distribution and line profile analysis diagram of the catalyst prepared in Example 4, Figure 5 (b) is the three-dimensional intensity distribution and line profile analysis diagram of the catalyst prepared in Example 7, Figure 5 (c) is a three-dimensional intensity distribution and line profile analysis diagram of the catalyst prepared in Example 11;

[0034] Figure 6 A schematic diagram of the molar ratio of the doping element to iron in the catalysts prepared in Example 4, Example 7 and Example 11;

[0035] Figure 7 X-ray diffraction patterns of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0036] Figure 8 The Fourier transform Fe K-edge R-space X-ray extended edge absorption fine structure spectra of the catalysts, FePc and iron foil prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0037] Fig. 9 It is a Fourier transform FeK-edge R-space X-ray extended edge absorption fine structure fitting result diagram of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0038] Fig.10 is the wavelet variation EXAFS analysis diagram, where: Fig.10 (a) is the wavelet variation EXAFS analysis diagram of the catalyst prepared in Comparative Example 1, Fig.10 (b) is the wavelet variation EXAFS analysis diagram of the catalyst prepared in Example 4, Fig.10 (c) is the wavelet variation EXAFS analysis diagram of the catalyst prepared in Example 7, Fig.10 (d) is the wavelet variation EXAFS analysis diagram of the catalyst prepared in Example 11;

[0039] Fig.11 Fe K-edge X-ray absorption near-edge structure spectra of the catalysts, Fe foil, FeO, Fe2O3 and Fe3O4 prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0040] Fig.12 It is a curve diagram of the change of 4-CP concentration in the process of activating PMS to degrade 4-CP by the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0041] Fig.13 This is a comparison chart of the degradation rate of 4-CP by the catalyst activated PMS prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0042] Fig.14 It is a comparison chart of the quenching experiment of 4-CP degradation by the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0043] Fig.15 is the EPR spectrum, where Fig.15 (a) is the EPR spectra of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 using TEMP, Fig.15 (b) is an EPR spectrum of DMPO used for the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0044] Fig.16 This is a comparison chart of the PMS consumption during the PMS degradation of 4-CP by the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0045] Fig.17 The catalyst activation PMS process produced by Comparative Example 1, Example 4, Example 7 and Example 11 1 O2 and Fe(IV)=O content and PMS utilization diagram;

[0046] Fig.18 It is the EIS curve diagram of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0047] Fig.19 It curve diagram of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0048] Fig. 20 It is the LSV curve diagram of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0049] Fig.21 The degradation rate of 4-CP by the catalyst PMS prepared in Examples 1 to 12, Fe IV =O / 1 Correlation diagram between O2 / electron transfer contribution rate and doping element / iron molar ratio;

[0050] Fig. 22 The degradation rate diagram of 4-CP by activated PMS of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 under different water quality conditions;

[0051] Fig.23 The degradation rate diagram of 4-CP by PMS activated by the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 under different pH conditions;

[0052] Fig.24 It is a graph showing the degradation rate of 4-CP by activated PMS of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 under different anion and cation conditions;

[0053] Fig.25 The experimental effect diagram of the continuous flow membrane device of the catalyst prepared in Comparative Example 1, Example 4, Example 7 and Example 11 in the process of activating PMS and degrading 4-CP under deionized water conditions;

[0054] Fig.26 It is a diagram showing the experimental effect of a continuous flow membrane device for activating the PMS degradation 4-CP process under the first wastewater condition using the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11;

[0055] Fig. 27 The experimental results of the continuous flow membrane device and the iron ion dissolution rate diagram of the catalyst prepared in Comparative Example 1, Example 4, Example 7 and Example 11 in the process of activating PMS and degrading 4-CP under the second wastewater condition;

[0056] Fig.28 This is a comparison chart of the degradation rates of different benzene derivatives and antibiotics by activating PMS with the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11. DETAILED DESCRIPTION

[0057] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0058] In the following examples, unless otherwise specified, all experimental methods mentioned are conventional methods; all reagents and materials mentioned, unless otherwise specified, can be obtained through commercial channels.

[0059] The present invention provides a method for preparing an iron single-atom catalyst with controllable doping of p-zone elements. By controlling the type of the doping source, the synthesis of a series of iron single-atom catalysts doped with different p-zone elements is achieved. In addition, by changing the dosage of the doping source, the preparation of iron single-atom catalysts with different dopant concentrations is further achieved, and is described in detail in Examples 1 to 12.

[0060] Example 1 Sulfur-doped iron single atom catalyst (0.09-FeS / CN) (10 wt%) was synthesized by the following method:

[0061] S1: 1 g of melamine was dissolved in 100 ml of deionized water at 80° C. to obtain a melamine solution; 0.8 g of cyanuric acid was dissolved in 120 ml of deionized water at 80° C. to obtain a cyanuric acid solution; 0.22 g of ferrous sulfate heptahydrate was dissolved in 60 ml of deionized water at 25° C. to obtain a ferrous sulfate solution.

[0062] S2: 0.1 ml of sulfuric acid and 0.14 g of oxalic acid were added to the ferrous sulfate solution and stirred at 25° C. for 10 min to form a uniform solution A.

[0063] S3: After adding the solution A to the cyanuric acid solution, stirring at 80°C for 10 minutes to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to carry out a coprecipitation reaction for 3 hours; after the reaction is completed, solid-liquid separation is achieved by suction filtration, and the precipitate is alternately washed with deionized water and ethanol for 3 times each to remove impurities; then, it is dried by forced air at 60°C for 8 hours to obtain a supramolecular precursor, and it is ground into a uniform powder.

[0064] S4: Under the protection of a high-purity argon atmosphere with a purity of 99.99%, the powdered supramolecular precursor was heated to 600°C at a heating rate of 5°C / min, kept for 4 hours and then cooled to room temperature to obtain a carbon nitride-supported sulfur-doped iron single-atom catalyst, denoted as 0.09-FeS / CN.

[0065] The sulfur-doped iron single-atom catalyst prepared in Example 1 had a measured sulfur-iron molar ratio of 0.09, and was therefore recorded as 0.09-FeS / CN.

[0066] Example 2 Sulfur-doped iron single atom catalyst (0.12-FeS / CN) (10 wt%)

[0067] Compared with Example 1, 0.2 ml of sulfuric acid and 0.3 g of oxalic acid were used in step (2) of this example, and the other steps were the same.

[0068] The measured sulfur-iron molar ratio of the sulfur-doped iron single-atom catalyst prepared in Example 2 is 0.12, so it is recorded as 0.12-FeS / CN.

[0069] Example 3 Sulfur-doped iron single atom catalyst (0.15-FeS / CN) (10 wt%)

[0070] Compared with Example 1, 0.3 ml of sulfuric acid was used in step (2) of this example, and the other steps were the same.

[0071] The sulfur-doped iron single-atom catalyst prepared in Example 3 had a measured sulfur-iron molar ratio of 0.15, and was therefore recorded as 0.15-FeS / CN.

[0072] Example 4 Sulfur-doped iron single atom catalyst (0.21-FeS / CN) (10 wt%)

[0073] Compared with Example 1, 0.4 ml of sulfuric acid was used in step (2) of this example, and the other steps were the same.

[0074] The measured sulfur-iron molar ratio of the sulfur-doped iron single-atom catalyst prepared in Example 4 is 0.21, so it is recorded as 0.21-FeS / CN.

[0075] Example 5 Phosphorus-doped iron single atom catalyst (0.09-FeP / CN) (10 wt%) was synthesized by the following method:

[0076] S1: 1 g of melamine was dissolved in 100 ml of deionized water at 80° C. to obtain a melamine solution; 0.8 g of cyanuric acid was dissolved in 120 ml of deionized water at 80° C. to obtain a cyanuric acid solution; 0.22 g of ferrous sulfate heptahydrate was dissolved in 60 ml of deionized water at 25° C. to obtain a ferrous sulfate solution.

[0077] S2: 0.1 ml of phosphoric acid and 0.14 g of oxalic acid were added to the ferrous sulfate solution and stirred at 25° C. for 10 min to form a uniform solution A.

[0078] S3: After adding the solution A to the cyanuric acid solution, stirring at 80°C for 10 minutes to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to carry out a coprecipitation reaction for 3 hours; after the reaction is completed, solid-liquid separation is achieved by suction filtration, and the precipitate is alternately washed with deionized water and ethanol for 3 times each to remove impurities; then, it is dried by forced air at 60°C for 8 hours to obtain a supramolecular precursor, and it is ground into a uniform powder.

[0079] S4: Under the protection of a high-purity argon atmosphere with a purity of 99.99%, the powdered supramolecular precursor was heated to 600°C at a heating rate of 5°C / min, kept for 4 hours and then cooled to room temperature to obtain a carbon nitride-supported phosphorus-doped iron single-atom catalyst, denoted as 0.09-FeP / CN.

[0080] The measured phosphorus-iron molar ratio of the phosphorus-doped iron single-atom catalyst prepared in Example 5 is 0.09, so it is recorded as 0.09-FeP / CN.

[0081] Example 6 Phosphorus-doped iron single atom catalyst (0.16-FeP / CN) (10 wt%)

[0082] Compared with Example 5, 0.2 ml of phosphoric acid and 0.3 g of oxalic acid were used in step (2) of this example, and the other steps were the same.

[0083] The measured phosphorus-iron molar ratio of the phosphorus-doped iron single-atom catalyst prepared in Example 6 is 0.16, and is therefore recorded as 0.16-FeP / CN.

[0084] Example 7 Phosphorus-doped iron single atom catalyst (0.23-FeP / CN) (10 wt%)

[0085] Compared with Example 5, 0.3 ml of phosphoric acid and 0.3 g of oxalic acid were used in step (2) of this example, and the other steps were the same.

[0086] The measured phosphorus-iron molar ratio of the phosphorus-doped iron single-atom catalyst prepared in Example 7 is 0.23, and is therefore recorded as 0.23-FeP / CN.

[0087] Example 8 Phosphorus-doped iron single atom catalyst (0.34-FeP / CN) (10 wt%)

[0088] Compared with Example 5, 0.4 ml of phosphoric acid was used in step (2) of this example, and the other steps were the same.

[0089] The measured phosphorus-iron molar ratio of the phosphorus-doped iron single-atom catalyst prepared in Example 8 is 0.34, and is therefore recorded as 0.34-FeP / CN.

[0090] Example 9 Boron-doped iron single atom catalyst (0.08-FeB / CN) (10 wt%) was synthesized by the following method:

[0091] S1: 1 g of melamine was dissolved in 100 ml of deionized water at 80° C. to obtain a melamine solution; 0.8 g of cyanuric acid was dissolved in 120 ml of deionized water at 80° C. to obtain a cyanuric acid solution; 0.22 g of ferrous sulfate heptahydrate was dissolved in 60 ml of deionized water at 25° C. to obtain a ferrous sulfate solution.

[0092] S2: 0.1 g of boric acid and 0.3 g of oxalic acid were added to the ferrous sulfate solution, and stirred at 25° C. for 10 min to form a uniform solution A.

[0093] S3: After adding the solution A to the cyanuric acid solution, stirring at 80°C for 10 minutes to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to carry out a coprecipitation reaction for 3 hours; after the reaction is completed, solid-liquid separation is achieved by suction filtration, and the precipitate is alternately washed with deionized water and ethanol for 3 times each to remove impurities; then, it is dried by forced air at 60°C for 8 hours to obtain a supramolecular precursor, and it is ground into a uniform powder.

[0094] S4: Under the protection of a high-purity argon atmosphere with a purity of 99.99%, the powdered supramolecular precursor was heated to 600°C at a heating rate of 5°C / min, kept for 4 hours and then cooled to room temperature to obtain a carbon nitride-supported boron-doped iron single atom catalyst, denoted as 0.08-FeB / CN.

[0095] The boron-doped iron single-atom catalyst prepared in Example 9 had a measured boron-iron molar ratio of 0.08, and was therefore recorded as 0.08-FeB / CN.

[0096] Example 10 Boron-doped iron single atom catalyst (0.16-FeB / CN) (10 wt%)

[0097] Compared with Example 9, 0.2 g of boric acid was used in step (2) of this example, and the other steps were the same.

[0098] The measured boron-to-iron molar ratio of the boron-doped iron single-atom catalyst prepared in Example 10 is 0.16, and is therefore recorded as 0.16-FeB / CN.

[0099] Example 11 Boron-doped iron single atom catalyst (0.28-FeB / CN) (10 wt%)

[0100] Compared with Example 9, 0.3 g of boric acid was used in step (2) of this example, and the other steps were the same.

[0101] The measured boron-to-iron molar ratio of the boron-doped iron single-atom catalyst prepared in Example 11 is 0.28, so it is recorded as 0.28-FeB / CN.

[0102] Example 12 Boron-doped iron single atom catalyst (0.39-FeB / CN) (10 wt%)

[0103] Compared with Example 9, 0.4 g of boric acid was used in step (2) of this example, and the other steps were the same.

[0104] The measured boron-iron molar ratio of the boron-doped iron single-atom catalyst prepared in Example 12 is 0.39, so it is recorded as 0.39-FeB / CN.

[0105] Comparative Example 1 Iron single atom catalyst (Fe / CN) (10 wt%) was synthesized by the following method:

[0106] S1: 1 g of melamine was dissolved in 100 ml of deionized water at 80° C. to obtain a melamine solution; 0.8 g of cyanuric acid was dissolved in 120 ml of deionized water at 80° C. to obtain a cyanuric acid solution; 0.22 g of ferrous sulfate heptahydrate was dissolved in 60 ml of deionized water at 25° C. to obtain a ferrous sulfate solution.

[0107] S2: 0.6 g of oxalic acid was added to the ferrous sulfate solution and stirred at 25° C. for 10 min to form a uniform solution A.

[0108] S3: After adding the solution A to the cyanuric acid solution, stirring at 80°C for 10 minutes to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to carry out a coprecipitation reaction for 3 hours; after the reaction is completed, solid-liquid separation is achieved by suction filtration, and the precipitate is alternately washed with deionized water and ethanol for 3 times each to remove impurities; then, it is dried by forced air at 60°C for 8 hours to obtain a supramolecular precursor, and it is ground into a uniform powder.

[0109] S4: Under the protection of a high-purity argon atmosphere with a purity of 99.99%, the powdered supramolecular precursor was heated to 600°C at a heating rate of 5°C / min, kept for 4 hours and then cooled to room temperature to obtain a carbon nitride-supported iron single-atom catalyst, denoted as Fe / CN.

[0110] Comparative Example 2 A graphite phase carbon nitride (CN) was synthesized by the following steps:

[0111] S1: 1 g of melamine was dissolved in 100 ml of deionized water at 80° C. to obtain a melamine solution; 0.8 g of cyanuric acid was dissolved in 120 ml of deionized water at 80° C. to obtain a cyanuric acid solution.

[0112] S2: adding the cyanuric acid solution to the melamine solution, stirring at 80° C. for 10 min, and then performing a coprecipitation reaction for 3 h; after the reaction is completed, solid-liquid separation is achieved by suction filtration, and the precipitate is alternately washed with deionized water and ethanol for 3 times each to remove impurities; then, the precipitate is dried by forced air at 60° C. for 8 h to obtain a supramolecular precursor, and the precursor is ground into a uniform powder.

[0113] S3: Under the protection of a high-purity argon atmosphere with a purity of 99.99%, the powdered supramolecular precursor was heated to 600°C at a heating rate of 5°C / min, kept at that temperature for 4 hours, and then cooled to room temperature to obtain graphite phase carbon nitride, denoted as CN.

[0114] Comparative Example 3 A sulfur-doped graphite phase carbon nitride (SCN) was synthesized by the following steps:

[0115] S1: Dissolve 1 g of melamine in 100 ml of deionized water at 80°C to obtain a melamine solution; dissolve 0.8 g of cyanuric acid in 120 ml of deionized water at 80°C to obtain a cyanuric acid solution; dissolve 0.3 ml of sulfuric acid in 30 ml of deionized water at 25°C to obtain a sulfuric acid solution.

[0116] S2: adding the sulfuric acid solution in S1 to the cyanuric acid solution, stirring evenly at 80°C for 10 minutes, then pouring the mixed solution into the melamine solution obtained in step S1, stirring for 3 hours to carry out a co-precipitation reaction; after the reaction is completed, achieving solid-liquid separation by suction filtration, and washing the precipitate alternately with deionized water and ethanol for 3 times each to remove impurities; then performing forced air drying at 60°C for 8 hours to obtain a supramolecular precursor, and grinding it into a uniform powder.

[0117] S3: Under the protection of a high-purity argon atmosphere with a purity of 99.99%, the powdered supramolecular precursor was heated to 600°C at a heating rate of 5°C / min, kept at that temperature for 4 hours, and then cooled to room temperature to obtain sulfur-doped graphite phase carbon nitride, denoted as SCN.

[0118] Comparative Example 4 A phosphorus-doped graphite phase carbon nitride (PCN) was synthesized by the following steps:

[0119] S1: Dissolve 1 g of melamine in 100 ml of deionized water at 80°C to obtain a melamine solution; dissolve 0.8 g of cyanuric acid in 120 ml of deionized water at 80°C to obtain a cyanuric acid solution; and dissolve 0.3 ml of phosphoric acid in 30 ml of deionized water at 25°C to obtain a phosphoric acid solution.

[0120] S2: adding the phosphoric acid solution in S1 to the cyanuric acid solution, stirring evenly at 80°C for 10 minutes, then pouring the mixed solution into the melamine solution obtained in step S1, stirring for 3 hours to carry out a co-precipitation reaction; after the reaction is completed, achieving solid-liquid separation by suction filtration, and washing the precipitate alternately with deionized water and ethanol for 3 times each to remove impurities; then performing forced air drying at 60°C for 8 hours to obtain a supramolecular precursor, and grinding it into a uniform powder.

[0121] S3: Under the protection of a high-purity argon atmosphere with a purity of 99.99%, the powdered supramolecular precursor was heated to 600°C at a heating rate of 5°C / min, kept at that temperature for 4 hours, and then cooled to room temperature to obtain phosphorus-doped graphite phase carbon nitride, denoted as PCN.

[0122] Comparative Example 5 A boron-doped graphite phase carbon nitride (BCN) was synthesized by the following steps:

[0123] S1: Dissolve 1 g of melamine in 100 ml of deionized water at 80°C to obtain a melamine solution; dissolve 0.8 g of cyanuric acid in 120 ml of deionized water at 80°C to obtain a cyanuric acid solution; dissolve 0.3 g of boric acid in 120 ml of deionized water at 25°C to obtain a boric acid solution.

[0124] S2: Add the boric acid solution described in S1 to the cyanuric acid solution, stir evenly at 80°C for 10 minutes, then pour the mixed solution into the melamine solution obtained in step S1, and stir for 3 hours to perform a co-precipitation reaction; after the reaction is completed, separate the solid and liquid by suction filtration, and wash the precipitate alternately with deionized water and ethanol for 3 times each to remove impurities; then dry it with air at 60°C for 8 hours to obtain a supramolecular precursor, and grind it into a uniform powder.

[0125] S3: Under the protection of a high-purity argon atmosphere with a purity of 99.99%, the powdered supramolecular precursor was heated to 600°C at a heating rate of 5°C / min, kept at that temperature for 4 hours, and then cooled to room temperature to obtain boron-doped graphite phase carbon nitride, denoted as BCN.

[0126] The schematic diagram of the structure of the catalyst prepared in Comparative Example 1, Example 4, Example 7 and Example 11 is as follows Figure 1 As shown. Melamine and cyanuric acid are organized into rod-shaped supramolecular precursors through supramolecular self-assembly processes, and sulfuric acid, phosphoric acid or boric acid are added as S sources, P sources or B sources, respectively. The process involves the decomposition and reorganization of the precursor components, and the resulting structure is uniform and stable, which helps to form a catalyst with good catalytic activity and stability. Finally, a high-temperature pyrolysis process under an argon atmosphere successfully synthesized a p-zone element controllably doped iron single-atom catalyst, including a sulfur-doped iron single-atom catalyst (e.g., 0.21-FeS / CN prepared in Example 4), a phosphorus-doped iron single-atom catalyst (e.g., 0.23-FeP / CN prepared in Example 7) and a boron-doped iron single-atom catalyst (e.g., 0.28-FeB / CN prepared in Example 11). Among them, the addition of an iron source and a doping element (S, P or B) to the melamine and melamine framework is the key to achieving the expected catalytic performance of the catalyst.

[0127] Figure 2This is a spherical aberration-corrected high-angle annular dark-field scanning transmission electron micrograph of the sulfur-doped iron single-atom catalyst (FeS / CN) prepared in Example 4 and a Fe and S element distribution spectrum. Figure 3 This is a spherical aberration-corrected high-angle annular dark-field scanning transmission electron micrograph of the phosphorus-doped iron single-atom catalyst (FeP / CN) prepared in Example 7 and a Fe and P element distribution spectrum. Figure 4 The spherical aberration-corrected high-angle annular dark-field scanning transmission electron micrograph and the Fe and B element distribution spectrum of the boron-doped iron single-atom catalyst (FeB / CN) prepared in Example 11. Figure 2 , Figure 3 and Figure 4 It was observed that FeS / CN, FeP / CN and FeB / CN all have lamellar structures, and the spherical aberration corrected high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) shows that the single iron atoms are dispersed in an atomic state on the carrier. The comprehensive visualization of the elemental composition and distribution in the sample was achieved by energy dispersive x-ray spectroscopy (EDX). The mapping results showed the uniform distribution of iron and doping elements, proving that B, P or S elements were successfully doped.

[0128] Figure 5 is the three-dimensional intensity distribution and line profile analysis diagram, where Figure 5 (a) is the three-dimensional intensity distribution and line profile analysis diagram of the sulfur-doped iron single atom catalyst (FeS / CN) prepared in Example 4, Figure 5 (b) is the three-dimensional intensity distribution and line profile analysis diagram of the phosphorus-doped iron single atom catalyst (FeP / CN) prepared in Example 7, Figure 5 (c) is the three-dimensional intensity distribution and line profile analysis diagram of the boron-doped iron single-atom catalyst (FeB / CN) prepared in Example 11. Figure 5 (a) Figure 5 (b) and Figure 5 (c) In-depth analysis of the microstructure of the iron single-atom catalyst. The 3D intensity distribution image visually demonstrates the distribution of iron atoms in the sample. The line profile analysis is from a selected area of ​​the spherical aberration-corrected high-angle annular dark-field scanning transmission electron microscopy image, highlighting the significant contrast between the iron atoms and the underlying support, confirming the dispersion of the iron atoms without any observable agglomeration. Figure 5 (a) Figure 5 (b) and Figure 5As shown in (c), the distance between iron atoms exceeds the Fe-Fe bond length (0.207nm), further confirming the single-atom nature of the catalyst. At the same time, the atomic distances were measured, where the average minimum distance between adjacent atoms of FeS / CN was 0.41nm, the average minimum distance between adjacent atoms of FeP / CN was 0.40nm, and the average minimum distance between adjacent atoms of FeB / CN was 0.37nm. This proves that the Fe SAC samples doped with different elements have structural consistency. The schematic diagram of the molar ratio of the doping element to iron of the sulfur-doped iron single atom catalyst prepared in Example 4, the phosphorus-doped iron single atom catalyst prepared in Example 7, and the boron-doped iron single atom catalyst prepared in Example 11 is shown in Figure 6 As shown, the inductively coupled plasma optical emission spectroscopy (ICP-OES) results quantified the mass fractions of iron and doping elements in the catalyst, where the Fe loading was approximately 10 wt%, and the molar ratio of the doping element to iron was calculated (e.g., B / Fe=0.28, P / Fe=0.23, S / Fe=0.21), further indicating that these elements were controllably incorporated into the catalyst.

[0129] The crystal planes of the carrier CN in each catalyst were analyzed by X-ray diffractometer. Figure 7 The X-ray diffraction of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11. Figure 7 It can be seen that Fe / CN, FeS / CN, FeP / CN and FeB / CN not only maintain the same structure as CN, but also do not show the characteristic diffraction peaks of iron nanoparticles, indicating that the iron in each catalyst exists in the form of small-sized atoms, which is consistent with the test results of spherical aberration electron microscopy.

[0130] Based on the above images and elemental analysis, it is proved that the iron single-atom catalyst with controllable doping element distribution is successfully synthesized. The successful doping of elements is important for the influence of the microscopic environment of the iron single atom. In order to further explore the atomic chemical state and coordination structure in Fe SAC, the iron single-atom catalyst (Fe / CN) prepared in Comparative Example 1, the sulfur-doped iron single-atom catalyst (FeS / CN) prepared in Example 4, the phosphorus-doped iron single-atom catalyst (FeP / CN) prepared in Example 7 and the boron-doped iron single-atom catalyst (FeB / CN) prepared in Example 11 are detected by X-ray absorption fine structure (XAFS) spectrum including X-ray absorption near-edge structure (XANES) and extended edge X-ray absorption fine structure spectrum (EXAFS) The coordination configuration is studied.

[0131] The Fourier transform Fe K-edge R-space X-ray extended edge absorption fine structure spectra of the catalysts, FePc and iron foil (Fefoil) prepared in Comparative Example 1, Example 4, Example 7 and Example 11 are shown in Figure 8 As shown, Fe / CN The peaks of Fe-N coordination are shown, while the peak changes of FeS / CN, FeP / CN and FeB / CN may be attributed to the additional features of Fe-S, Fe-P and Fe-B bonds, respectively. There is no Fe-Fe scattering peak near , which indicates that the iron atoms are successfully dispersed in the support as single atoms without forming clusters. Figure 8 The R-space X-ray extended edge absorption fine structure spectrum curve of the Rieber transform Fe K-edge shown in the figure is fitted, and the fitting result is shown in Fig. 9 It is shown that Fe / CN presents a symmetric coordination environment of Fe-N4 with a coordination number of 4, while FeP / CN, FeS / CN, and FeB / CN present asymmetric coordination environments of Fe-S1N3, Fe-P1N3, and Fe-B1N3, respectively. Since the wavelet transform (WT) has a strong resolution in both K-space and R-space, the EXAFS oscillation of Fe K-edge EXAFS is further discussed. Fig.10 is the wavelet variation EXAFS analysis diagram, where Fig.10 (a) is the wavelet variation EXAFS analysis diagram of the catalyst prepared in Comparative Example 1, Fig.10 (b) is the wavelet variation EXAFS analysis diagram of the catalyst prepared in Example 4, Fig.10 (c) is the wavelet variation EXAFS analysis diagram of the catalyst prepared in Example 7, Fig.10 (d) is the wavelet variation EXAFS analysis diagram of the catalyst prepared in Example 11; Fig.10 (a) Fig.10 (b) Fig.10 (c) and Fig.10 (d) shows the WT contour map of Fe / CN. There is only one maximum intensity at the Fe-N bond. For FeS / CN and FeP / CN, due to the existence of Fe-S coordination, this will shift to Chuhe Similarly, FeB / CN also shifted significantly. Fe k-edge X-ray absorption near-edge structure (XANES) Fig.11As shown in the figure, the edge positions of Fe / CN, FeS / CN, FeP / CN, and FeB / CN were compared with the oxidation states of iron in standard samples such as Fe foil, Fe2O3, and Fe3O4. The absorption edge and transition energy of Fe in the four materials are between ferrous oxide and ferric oxide, indicating that the average valence state of the catalyst is between +2 and +3. It is worth mentioning that FeP / CN and FeB / CN have lower oxidation states, which may be related to the higher contribution rate of high-valent iron active species shown in the following experimental results.

[0132] Application Example 1

[0133] The effect of four different catalysts (Fe / CN, FeS / CN, FeP / CN and FeB / CN) on the degradation efficiency of parachlorophenol (4-CP) was explored. A saturated aqueous solution of 4-CP was added to 50 ml of deionized water, and the initial concentration of the 4-CP solution was accurately adjusted to 0.1 mmol / L. 25 mg of four different catalysts were weighed respectively: the catalysts prepared by Comparative Example 1, Example 4, Example 7 and Example 11. The above catalysts were added to containers containing 0.1 mmol / L 4-CP solution. Ultrasonic dispersion was used to ensure that the catalyst was uniformly dispersed in the solution, and then the containers were placed on a magnetic stirrer to maintain a continuous stirring state until the adsorption reaction was balanced between the solid and the liquid. A saturated solution of PMS was added to control the initial concentration of PMS to 0.5 mmol / L. From the moment the saturated solution of PMS was added, the timing was started, and a clean syringe was used to sample at specific time points (0, 0.3, 0.6, 1, 2, 3, 5 and 10 min). The sample was filtered through a 0.22 μm filter membrane for solid-liquid separation, and the separated solution was transferred to an ampoule containing 10% methanol solution by volume to stabilize the sample state. Finally, the concentrations of 4-CP and PMS in the solution were accurately determined using high performance liquid chromatography (HPLC) and ultraviolet spectrophotometer.

[0134] Fig.12 The curves showing the change of 4-CP concentration in the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 during the process of activating PMS to degrade 4-CP are shown. The degradation curves all show the characteristics of first-order kinetics, such as Fig.13 As shown in Figure 2, the degradation rate of Fe / CN is calculated to be 0.417 min -1 The degradation rate of FeS / CN catalyst is 0.423min -1 The degradation rate of FeP / CN catalyst is 0.915min -1 The degradation rate of FeB / CN catalyst is 1.871min -1 .from Fig.13It can be seen that Fe / CN, as the control group, has the lowest degradation efficiency, which confirms the importance of doping elements in improving the degradation performance of materials. It shows that the doping of p-zone elements can increase the degradation rate of 4-CP in solution by the catalyst to varying degrees, among which B doping has the most significant improvement on the degradation effect, which may be attributed to the unique structure of FeB / CN materials. These characteristics may enhance its adsorption capacity and catalytic activity.

[0135] Application Example 2

[0136] A saturated aqueous solution of 4-CP was added to an 80ml beaker containing 50ml deionized water to ensure that the initial concentration of 4-CP was 0.1mmol / L. Various quenching experiments were added, wherein the concentrations of methanol and tert-butyl alcohol were 500mmol / L, the concentration of nitroblue tetrazolium was 5mmol / L, the concentration of methylphenyl sulfoxide was 5mmol / L, and the concentration of sodium azide was 5mmol / L. Subsequently, 25mg of the catalysts prepared in Comparative Example 1, Example 4, Example 7, and Example 11 were weighed and added to a 0.1mmol / L 4-CP solution containing a quencher of the corresponding concentration. Ultrasonic dispersion and magnetic stirring were used to ensure that the adsorption reaction equilibrium was reached between the solid and the liquid. After adding the saturated PMS solution and starting the timing, a syringe was used to take samples at different time points (0, 0.3, 0.6, 1, 2, 3, 5, and 10min), and after solid-liquid separation with a 0.22 micron filter membrane, an ampoule containing a 10% methanol solution by volume was placed. The concentration of 4-CP in the solution was determined by high performance liquid chromatography.

[0137] The comparison of the quenching experiments of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 for degradation of 4-CP is shown in the figure below. Fig.14 As shown, it was observed that when methanol (MeOH), tert-butyl alcohol (TBA), nitro blue tetrazolium (NBT), sodium azide (NaN3) and methyl phenyl sulfoxide (DMSO) were added to the Fe / CN / PMS / 4-CP system, the degradation of 4-CP was basically uninhibited. However, when sodium azide (NaN3) was added, the degradation of 4-CP was significantly inhibited. Under the same experimental conditions, sodium azide and methyl phenyl sulfoxide significantly inhibited the degradation of 4-CP in both FeS / CN / PMS / 4-CP and FeP / CN / PMS / 4-CP systems. In contrast, methanol, tert-butyl alcohol and nitro blue tetrazolium had no effect on the degradation of 4-CP in the FeB / CN / PMS / 4-CP system, while sodium azide and methyl phenyl sulfoxide partially inhibited the degradation of 4-CP in the system, but did not completely inhibit it. Combined with further experiments, the electron transfer path will also have an effect on the degradation. Further analysis showed that Fe / CN activated PMS mainly produced 1 O2. In contrast, FeS / CN activation of PMS mainly produces FeIV =O and 1 O2, the contribution rates were 41% and 59% respectively; FeP / CN activated PMS is also the main source of Fe IV =O and 1 O2, the contribution rates were 76% and 24% respectively; and FeB / CN activated PMS in addition to producing Fe IV =O and 1 O2, the contribution of the electron transfer pathway is 35%.

[0138] In order to further explore the reasons for the differences in the degradation effects of different catalysts on organic pollutants under the reaction conditions, the main active substances produced during the activation of persulfate (PMS) were analyzed by electron paramagnetic resonance (EPR) test. The EPR spectra of the iron single atom catalyst prepared in Comparative Example 1, the sulfur-doped iron single atom catalyst prepared in Example 4, the phosphorus-doped iron single atom catalyst prepared in Example 7, and the boron-doped iron single atom catalyst prepared in Example 11 during the activation of PMS are shown in Figure 1. Fig.15 As shown (TEMP and DMPO were present as capture agents, respectively). Fig.15 is the EPR spectrum, where Fig.15 (a) is the EPR spectra of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 using TEMP, Fig.15 (b) is the EPR spectra of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 using DMPO; Fig.15 (a) shows that EPR analysis using 2,2,6,6-tetramethylpiperidine (TEMP) as a spin trapping agent reveals that the TEMP- 1 The O2-related triplet signal indicates the generation of singlet oxygen in this system. In particular, the combinations of TEMP+PMS+FeS / CN and TEMP+PMS+Fe / CN show strong signals, indicating that the FeS / CN and Fe / CN catalysts are very effective in generating singlet oxygen. Fig.15 The electron paramagnetic resonance (EPR) spectrum shown in (b) shows that when 5,5-dimethyl-1-pyrrolidine N-oxide (DMPO) is used as a capture agent, the electron paramagnetic resonance spectrum (EPR) detects a DMPOX signal. This peak is produced by the oxidation of DMPO by a strong oxidizing substance. According to literature reports and the analysis of the quenching experimental results in the previous article, this substance is very likely a high-valent iron species. The peak intensity comparison shows that the P-doped catalyst (FeP / CN) may be more inclined to generate high-valent iron, which is consistent with the results of the quenching experiment in the previous article.

[0139] In addition, the change of PMS concentration in each reaction system over time was further monitored. The comparison of PMS consumption during the PMS degradation of 4-CP by the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 is shown in FIG. Fig.16 As shown in the figure, the consumption of FeB / CN is greatly affected by pollutants. After adding pollutants, the consumption of PMS can be increased by 40%. At the same time, it shows the best performance. This result suggests that there may be an electron transfer pathway in the system. In the process of activating persulfate (PMS), 1 O2 and Fe IV =O are two important active substances. Using DPBF as a probe in the quantitative reaction system 1 The content of O2 can be measured in Fe / CN / PMS, FeS / CN / PMS, FeP / CN / PMS and FeB / CN / PMS systems. 1 The contents of O2 were 0.13mmol, 0.11mmol, 0.083mmol and 0.060mmol respectively. Using PMSO conversion rate as an indicator of high-valent iron, the quantitative results are as follows Fig.17 shown. Fig.17 The catalyst activation PMS process produced by Comparative Example 1, Example 4, Example 7 and Example 11 1 The quantitative results show that Fe in Fe / CN / PMS, FeS / CN / PMS, FeP / CN / PMS and FeB / CN / PMS systems IV =O content is 0.004mmol, 0.036mmol, 0.10mmol and 0.015mmol respectively. However, in the FeB / CN / PMS system 1 O2 and Fe IV =O has the lowest total yield, which is contradictory to its best effect. However, according to the quenching experiment results mentioned above, it is more likely that there are other pathways for pollutant degradation in this system, such as electron transfer pathways. Combining the content of each active species generated, the component analysis showed that when no catalyst was added, the PMS utilization rates in Fe / CN / PMS, FeS / CN / PMS, FeP / CN / PMS and FeB / CN / PMS systems were 43.9%, 46.8%, 45.5% and 31.3%, respectively.

[0140] The electrochemical test results provide strong evidence for the existence of electron transfer pathways in the process of FeB / CN activation of PMS. Fig.18 : is the EIS curve diagram of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11, Fig.19It curve diagram of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11, Fig. 20 : is the LSV curve diagram of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11; Fig.18 , Fig.19 and Fig. 20 As shown, the potential versus time plot shows that FeB / CN has a significant current response after the introduction of PMS and pollutants. This change in current density is attributed to the formation of reactive surface complexes that facilitate the transfer of electrons from adsorbed organic pollutants to activated PMS. The negative current signal in the presence of both PMS and organic substrates indicates that electrons are transferred from the organic substrate (as an electron donor) to the activated PMS (as an electron acceptor). As observed in the LSV and EIS curves, FeB / CN has the best conductivity and the lowest resistance, indicating that the catalyst has the potential to facilitate the transfer of electrons from the solution to PMS. This observation is consistent with the electron transfer mechanism, where the catalyst acts as a conductive bridge to mediate electron transfer between organic pollutants and persulfate ions.

[0141] The effects of different dopant concentrations on the non-radical pathway of persulfate activation were further investigated. The degradation rates of 4-CP, Fe IV =O / 1 The correlation diagram between O2 / electron transfer contribution rate and doping element (S, P, B) / iron molar ratio, such as Fig.21 Initially, in the absence of dopants, the system completely relied on the intrinsic properties of the iron catalyst for persulfate activation. The introduction of dopants triggered a shift to a non-radical mechanism, which became increasingly prominent with increasing molar ratios of S / Fe, P / Fe, and B / Fe. Specifically, with increasing S doping levels, 1 The contribution rate of O2 increases, the increase of P doping leads to the increase of the contribution rate of high-valent iron, and B doping increases the contribution of the electron transfer pathway. This series of quenching experimental results show that the doping of different elements (S, P, B) is indeed an important reason for the transformation of the non-radical pathway during the peroxymonosulfate activation process.

[0142] Application Example 3

[0143] The saturated aqueous solution of 4-CP was added to several 80mL beakers containing 50mL of deionized water (DI water), tap water, ground water and wastewater, so that the initial concentration of 4-CP was 0.1mmol / L. 25mg of the catalysts prepared from Comparative Example 1, Example 4, Example 7 and Example 11 were weighed and added to the 0.1mmol / L 4-CP solution, and after ultrasonic dispersion, they were placed on a magnetic stirrer to maintain continuous stirring. After the adsorption reaction equilibrium between the solid and the liquid was reached, the saturated solution of PMS was added to make the initial concentration of PMS 0.5mmol / L. In addition, when the saturated solution of PMS was added, the timing was started, and a clean syringe was used to sample at 0, 0.3, 0.6, 1, 2, 3, 5 and 10min, respectively, and after solid-liquid separation with a 0.22 micron filter membrane, it was placed in an ampoule containing a 10% methanol solution by volume. Fig. 22 The degradation rate of 4-CP by PMS activated by the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 under different water quality conditions is shown in FIG. Fig. 22 It can be clearly seen that the FeB / CN catalyst showed high removal efficiency in all tested water bodies. Fig.23 The degradation rate of 4-CP by PMS activated by the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 under different pH conditions is shown in FIG. Fig.23 It can be seen that within the pH range of 4.95 to 10.98, its removal efficiency remains relatively stable. This shows that the FeB / CN catalyst has good pH adaptability and stability, and can maintain high efficiency in removing chlorophenols under different water quality conditions, showing its potential for application in the field of water treatment, especially in situations where it is necessary to adapt to variable water quality conditions. In the process of water treatment, various ions (such as Cl - , HCO3 - , SO4 2- , NO3 - , H2PO4 2- ions) may exist in the solution, and these ions may interact with the catalyst surface, thereby affecting the activity and selectivity of the catalyst. The degradation rate of 4-CP activated by PMS under different anion and cation conditions for the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 is shown in FIG. Fig.24 As shown, even in the presence of a variety of inorganic anions or cations, the degradation efficiency of the catalyst for 4-chlorophenol was not significantly affected. This shows that the four catalysts have good selectivity and stability and can effectively catalyze the degradation of pollutants in complex water environments.

[0144] In order to verify the stability of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11, a continuous flow membrane device experiment was conducted. The experimental effect diagram of the continuous flow membrane device of the catalysts prepared in Comparative Example 1, Example 4, Example 7 and Example 11 in the process of activating PMS and degrading 4-CP under deionized water (DI water) conditions is shown in the following figure: Fig.25 As shown; Comparative Example 1, Example 4, Example 7 and Example 11 prepared by the catalyst activated PMS degradation 4-CP process under the first wastewater (Wastewater 1) continuous flow membrane device experimental effect diagram as shown Fig.26 As shown; Comparative Example 1, Example 4, Example 7 and Example 11 prepared by the catalyst activation PMS degradation 4-CP process under the second wastewater (Wastewater 2) continuous flow membrane device experimental effect and iron ion dissolution rate diagram as shown Fig. 27 As shown. Fig.25 , Fig.26 and Fig. 27 As shown, the device experiment can achieve high-efficiency removal of chlorophenol, which indicates that the expansion from small scale to large scale is successful. In the FeB / CN system, the chlorophenol concentration drops rapidly, indicating that the FeB / CN catalyst is very effective in the degradation process, and the iron ion dissolution rate is less than 5% of the iron loading in the catalyst. Therefore, the catalyst has good reusability in the application of chlorophenol wastewater treatment, effectively reducing the operating cost.

[0145] Application Example 4

[0146] Degradation experiments were conducted on a series of different pollutants, including CP (chlorophenol), AN (aniline), PNP (p-nitrophenol), HBA (p-hydroxybenzoic acid), PhOH (phenol), 2,4-DCP (2,4-di-4-CP), NB (nitrobenzene), BA (benzoic acid), LEV (levofloxacin), CIP (ciprofloxacin) and NOX (norfloxacin). These pollutants represent different chemical properties, such as phenols, amines, nitro compounds, antibiotics and halogenated aromatic compounds. First, saturated aqueous solutions of these phenolic compounds were added to 80 ml beakers containing 50 ml of deionized water to ensure that the initial concentration was uniformly 0.1 mmol / L. 25 mg of catalyst was weighed, respectively from the preparation processes of Comparative Example 1, Example 4, Example 7 and Example 11. After the catalyst was added to the solution containing the corresponding pollutants, ultrasonic dispersion was used to ensure that the catalyst was fully mixed with the solution, and it was placed on a magnetic stirrer and kept stirring to promote the adsorption reaction between the solid and the liquid to reach equilibrium. A saturated solution of PMS was added, and the initial concentration of PMS was 0.5mmol / L. The timing started from the moment PMS was added, and samples were taken at specific time points of 0, 0.3, 0.6, 1, 2, 3, 5, and 10min using a clean syringe. After solid-liquid separation treatment using a 0.22-micron filter membrane, each sample was transferred to an ampoule containing a 10% methanol solution to prevent degradation of phenolic substances during the analysis. Finally, a high performance liquid chromatography (HPLC) was used to accurately determine the pollutant concentration. From Fig.28 It can be seen that FeB / CN still maintains the best degradation effect on different pollutants. In addition, the PMS utilization rate is significantly affected by pollutants and is consistent with the degradation effect of pollutants, further indicating that the electron transfer pathway is a key factor in the degradation of pollutants.

[0147] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A p-block element controllably doped iron single atom catalyst, characterized in that: The p-zone element controllably doped iron single atom catalyst is prepared by the following method: S1: dissolving melamine in deionized water at 70-90° C. to obtain a melamine solution; dissolving cyanuric acid in deionized water at 70-90° C. to obtain a cyanuric acid solution; dissolving ferrous sulfate heptahydrate in deionized water at 20-30° C. to obtain a ferrous sulfate solution; the molar ratio of melamine, cyanuric acid and ferrous sulfate is 1:0.5-0.9:0.1-0.5; S2: adding sulfuric acid and oxalic acid to the ferrous sulfate solution, and stirring at 20-30° C. for 5-10 min to form a solution A; the molar ratio of the sulfuric acid, oxalic acid and ferrous sulfate is 1:0.8-1:0.2-0.8; S3: adding the solution A to the cyanuric acid solution, stirring at 70-90° C. for 5-10 min to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to perform a coprecipitation reaction for 2-4 h; After the reaction is completed, the solid-liquid separation is achieved by suction filtration, and the precipitate is washed; then, the precipitate is dried by forced air at 55 to 60° C. for 6 to 8 hours to obtain a supramolecular precursor, which is then ground into a uniform powder; S4: Under the protection of argon atmosphere, the powdered supramolecular precursor is heated to 550-600°C, kept at this temperature for 3-5 hours and then cooled to room temperature to obtain an iron single atom catalyst with controllable doping of p-block elements, denoted as FeS / CN.

2. A p-block element controllably doped iron single atom catalyst, characterized in that: The p-zone element controllably doped iron single atom catalyst is prepared by the following method: S1: dissolving melamine in deionized water at 70-90° C. to obtain a melamine solution; dissolving cyanuric acid in deionized water at 70-90° C. to obtain a cyanuric acid solution; dissolving ferrous sulfate heptahydrate in deionized water at 20-30° C. to obtain a ferrous sulfate solution; the molar ratio of melamine, cyanuric acid and ferrous sulfate is 1:0.5-0.9:0.1-0.5; S2: adding oxalic acid and phosphoric acid to the ferrous sulfate solution, and stirring at 20-30° C. for 5-10 min to form a solution A; the molar ratio of the phosphoric acid, oxalic acid and ferrous sulfate is 1:0.8-1:0.2-0.8; S3: adding the solution A to the cyanuric acid solution, stirring at 70-90° C. for 5-10 min to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to perform a coprecipitation reaction for 2-4 h; After the reaction is completed, the solid-liquid separation is achieved by suction filtration, and the precipitate is washed; then, the precipitate is dried by forced air at 55 to 60° C. for 6 to 8 hours to obtain a supramolecular precursor, which is then ground into a uniform powder; S4: Under the protection of an argon atmosphere, the powdered supramolecular precursor is heated to 550-600°C, kept at this temperature for 3-5 hours, and then cooled to room temperature to obtain an iron single atom catalyst with controllable doping of p-block elements, which is denoted as FeP / CN.

3. A p-block element controllably doped iron single atom catalyst, characterized in that: The p-zone element controllably doped iron single atom catalyst is prepared by the following method: S1: dissolving melamine in deionized water at 70-90° C. to obtain a melamine solution; dissolving cyanuric acid in deionized water at 70-90° C. to obtain a cyanuric acid solution; dissolving ferrous sulfate heptahydrate in deionized water at 20-30° C. to obtain a ferrous sulfate solution; the molar ratio of melamine, cyanuric acid and ferrous sulfate is 1:0.5-0.9:0.1-0.5; S2: adding boric acid to the ferrous sulfate solution and stirring at 20-30° C. for 5-10 min to form a solution A; the molar ratio of the boric acid, oxalic acid and ferrous sulfate is 1:0.8-1:0.2-0.8; S3: adding the solution A to the cyanuric acid solution, stirring at 70-90° C. for 5-10 min to obtain a mixed solution B; then adding the mixed solution B to the melamine solution to perform a coprecipitation reaction for 2-4 h; After the reaction is completed, the solid-liquid separation is achieved by suction filtration, and the precipitate is washed; then, the precipitate is dried by forced air at 55 to 60° C. for 6 to 8 hours to obtain a supramolecular precursor, which is then ground into a uniform powder; S4: Under the protection of argon atmosphere, the powdered supramolecular precursor is heated to 550-600°C, kept at this temperature for 3-5 hours and then cooled to room temperature to obtain an iron single atom catalyst with controllable doping of p-block elements, denoted as FeB / CN.

4. Use of a p-block element controllably doped iron single atom catalyst according to claim 1, 2 or 3 for removing phenolic benzene derivatives from surface water, characterized in that: Specifically, the iron single atom catalyst with controllable doping of p-zone elements and permonosulfate are poured into a surface water body containing phenolic benzene series, the water temperature is 20-30°C, and the reaction is stirred for 10-15 minutes to complete the removal of phenolic benzene series in the surface water body; the dosage of the iron single atom catalyst with controllable doping of p-zone elements is 0.2-0.6 g / L; the dosage of the permonosulfate is 100-600 μmol / L; the concentration of the phenolic benzene series in the surface water body is 0-200 μmol / L.

5. The use according to claim 4, characterized in that: The phenolic benzene series compound is phenol, p-chlorophenol, p-hydroxybenzoic acid or p-nitrophenol.

Citation Information

Patent Citations

  • Monatomic catalyst for activating persulfate to generate pure singlet oxygen as well as preparation method and application thereof

    CN113058635A

  • FeP-loaded P-doped g-C3N4 material as well as preparation method and application thereof

    CN116618075A

  • Catalyst with controllable iron atom spacing and application thereof

    CN116803517A

  • Fully-exposed monatomic catalyst as well as preparation method and application thereof

    CN116984020A

  • Iron monatomic catalyst for efficiently degrading fluoroquinolone antibiotics and defluorinating and application of iron monatomic catalyst

    CN118767965A